2020
DOI: 10.3389/fphar.2020.00147
|View full text |Cite
|
Sign up to set email alerts
|

Modular Characteristics and Mechanism of Action of Herbs for Endometriosis Treatment in Chinese Medicine: A Data Mining and Network Pharmacology–Based Identification

Abstract: could also regulate VEGF signaling, toll-like reporter signaling, NF-kB signaling, MAPK signaling, PI3K-Akt signaling, and the HIF-1 signaling pathway, among others. Synergies often exist in herb pairs and herbal prescriptions. In conclusion, we identified some important targets, target pairs, and regulatory networks, using bioinformatics and data mining. The combination of data mining and network pharmacology may offer an efficient method for drug discovery and development from herbal medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 107 publications
(99 reference statements)
0
26
0
Order By: Relevance
“…In addition, MAPK14 plays a role in androgen biosynthesis [ 86 ]. The expression of MAPK14 has been found in patients with endometriosis and polycystic ovary syndrome [ 86 , 87 ]. Our result suggested that Jingshu granules may promote ovulation by targeting MAPK14 in the VEGF signaling pathway in the therapy of ovarian cysts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MAPK14 plays a role in androgen biosynthesis [ 86 ]. The expression of MAPK14 has been found in patients with endometriosis and polycystic ovary syndrome [ 86 , 87 ]. Our result suggested that Jingshu granules may promote ovulation by targeting MAPK14 in the VEGF signaling pathway in the therapy of ovarian cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Our convergent compound set found further overlap and potential validation when we compared it with published studies: For example, ginsenosides, sitosterol and arachidonic acid metabolites converge between our study ( Sun and Yang, 2019 ) and that of Sun and Yang (Fufang Danshen formulation). A study by Zheng et al ( Zheng et al, 2020 ) of endometriosis pain formulations overlapped with our in numerous terpenes, gingerols, and sitosterol). Huang et al ( Huang et al, 2017 ) studied dysmenorrheal pain (Xuangui formulation) and identified gingerols, terpenes, and arachidonic acid metabolites that overlap with our findings.…”
Section: Resolution: Viable Implementation Models and Research Imperamentioning
confidence: 99%
“…Hence, we further selected the major ingredients based on the literature to identify the potential therapeutic effects. Although some ingredients, such as volatile oil have lower DL values, they were selected because the effect had been experimental verification (Zheng et al, 2020). Meanwhile, the chemical information of these ingredients (structure, specification name, and CID number) for computational analysis was also collected according to the PubChem (https://pubchem.ncbi.nlm.nih.gov/) and DrugBank (https://www.drugbank.ca/drugs).…”
Section: Screening Of Bioactive Ingredients From the Mature Pericarp mentioning
confidence: 99%